STUDENT LEARNING ACHIEVEMENTS REVIEWED FROM PARENTAL ATTENTION, INDEPENDENCE, EMOTIONAL INTELLIGENCE, AND MOTIVATION (Study at SMP Batik Surakarta) - Indang Sari Handayani; Ida Aryati; Sarsono Sarsono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the simultaneous and partial influence of the variables of parents attention, independence, emotional intelligence and motivation students' learning achievements at SMP Batik Surakarta. This research was conducted at SMP Batik Surakarta with the object of analysis of grade IX students. This research method uses a quantitative descriptive research design with a sample of 80 students. Sampling techniques using purposive sampling techniques. Data collection using questionnaires. Data analysis techniques using statistical analysis are multiple linear regression tests, F tests, t-tests, and determination coefficients. The results showed that parental attention, learning independence, emotional intelligence and motivation influenced the learning achievements of grade IX students of SMP Batik Surakarta by 61.9%. In comparison, 38.1% was influenced by other variables not studied, such as learning interests, environment, peers or teacher competencies and others.